Evaluation of temperature of preparations served in a Food and Nutrition Unit (Research, Society and Development, 2019)
The monitoring of temperatures is an indispensable conduct to ensure food safety and should be observed as a way to prevent microbial multiplication, needing to be constantly performed. The present study had the objective of evaluating the temperature of the lunch preparations of a Food and Nutrition Unit of a Federal Education Institution, according to the current legislation. The temperatures of 43 hot preparations and 12 cold preparations were measured during 12 days at lunch time: beginning, middle and end of the distribution. Temperatures as rice / beans presented a 100% agreement with the values recommended by the current legislation. On the other hand, the preparations such as garnishes and salads presented a disagreement in their temperatures, with an adequacy index of 0% to 66.7%. Temperature logs and adequate paper filling are useful for monitoring and quality control of the preparations served, encouraging the adoption of measures that help to maintain temperatures within the recommended range. Considering the Food and Nutrition Unit evaluated, the acquisition of a thermal counter for cold preparations would be a necessary corrective measure to be implemented.